Emotional intelligence and entrepreneurial intention among university undergraduates in Nigeria: Exploring the mediating roles of self-efficacy domains - Kenechukwu Joshua Nwibe; Theresa Chinyere Ogbuanya (Journal of Innovation and Entrepreneurship, 2024)
How emotional competencies influence entrepreneurial behaviour especially among college students remains an under-researched subject in the entrepreneurship literature. In a unique perspective, this study examined the mediating roles of self-efficacy belief dimensions in the relationship between emotional intelligence and entrepreneurial intention of Electrical/Electronics Technology Education (EETE) students. The study was carried out among 192 EETE university students in 4 federal universities in South-East Nigeria. The hypothesized causal relationships based on literature were tested using covariance-based structural equation modelling (CB-SEM). Andrew Hayes' PROCESS plugin in SPSS was used to simultaneously estimate the mediating effects of the self-efficacy components (perceived competence, perceived control, and perceived persistence). Data analysis results revealed that emotional intelligence had a significant positive effect on entrepreneurial intention in isolation, while the direct effect of emotional intelligence in the structural (mediation) model was not significant. Out of the three dimensions of self-efficacy, perceived competence and perceived persistence had significant partial mediating effects. The implications of the findings and recommendations were discussed.
Keywords: 650; Electrical/Electronics Technology Education; Emotional intelligence; Entrepreneurial intention; Self-efficacy belief